Intraoperative prevention of postoperative hypoparathyroidism - Vabalayte, Kristina; Romanchishen, Anatoly; Somova, Aleksandra (Frontiers in Endocrinology, 2023)
Background. In the Russian Federation, about 30,000 thyroid surgeries are performed each year. Surgeries are generally safe due to existing methods that minimize postoperative complications. However, there is currently no single, reliable method to prevent postoperative hypoparathyroidism. This complication is frequently reported and poses health and life-threatening risks to patients. This study aims to evaluate the effectiveness of intraoperative ICG-angiography and intrathyroid injection of Brilliant Green in preventing postoperative hypoparathyroidism. Material and methods. A total of 143 thyroidectomies were performed. Patients were divided into three groups: intraoperative angiography was used in 24 cases; Brilliant Green was administered in 58 cases to help identify parathyroid glands (PTGs); and visual assessment was used for parathyroid preservation in 61 cases. Calcium levels were measured in all patients both before and after surgery. Results: Pre- and post-operative calcium levels were: 2.370.14 mmol/l and 2.270.17 mmol/l in group 1, 2.380.16 mmol/l and 2.210.16 mmol/l in group 2, and 2.390.17 mmol/l and 2.180.19 mmol/l in group 3. Postoperative hypocalcemia was more prominent in group 3, where PTGs were estimated visually, compared to the other two groups. Differences in postoperative calcium levels between group 1 and group 3 were statistically significant (p<0,05). Pre- and postoperative parathormone (PTH) levels were 6.20.4 pg/mL in group 1, 5.60.57 pg/mL in group 2, 3.50.32 pg/mL in group 3. Postoperative PTH levels significantly differed between groups 1 and 3 (p<0.01) and between groups 2 and 3 (p<0.05). Conclusions. ICG-angiography and Brilliant Green intrathyroid injection are both safe methods for identifying and preserving parathyroid glands. The severity of hypocalcemia and hypoparathyroidism in group 3 highlights the need to develop new methods in endocrine surgery to improve patient outcomes.